AN OPTIMIZED KINETIC SPECTROPHOTOMETRIC METHOD FOR THE RAPID AND ACCURATE DETERMINATION OF CEFOPERAZONE IN URINE AND TAP WATER SAMPLES - CESAR SOTO; Renato Saavedra; David Contreras; Diego Oyarzún; Cristián Poza (Journal of the Chilean Chemical Society, 2025)
This study presents a new approach for quantifying the antibiotic cefoperazone (CPZ) in spiked urine and tap water samples using an indirect kineticspectrophotometry method. The method involves the oxidation of CPZ by permanganate (MnO4-) in an alkaline media. The progress of the reactionis monitored by tracking the increase in manganate (MnO42- ) at 610 nm. The optimization of chemical-dependent variables was achieved through the utilization of multivariate statistical methods. The optimized values were 5 minutes of reaction time, KMnO4 of 1.11 · 10 -3 mol L−1, and NaOH of0.27 mol L−1. Under these conditions, calibration curves were constructed. The detection limits obtained in urine and tap water spiked samples were3.75 · 10−7 mol L−1 and 3.74 · 10−7 mol L−1, respectively. The results showed that intraday and interday recoveries ranged from 98.25 to 102.7%, indicating acceptable differences between observed and expected values according to the confidence percentage established as a criterion of acceptability; thus, demonstrating repeatability in results as well as satisfactory accuracy for this kinetic analytical method.